In Pursuit of a Different Revolution: Russian Populists of the Seventies Generation in 1917. Issue 3 (23rd October 2017) - Eklof, Ben; Saburova, Tatiana
Abstract : Nikolai Charushin and Vera Figner, both populists of the "1870s generation, " late in their lives played a role in the events of 1917, responding first with tempered enthusiasm, and then with trepidation over the growing chaos and polarization that led up to the Bolshevik revolution in October. Despite their efforts, such populists ended up on the losing side, and have often been criticized for misreading the situation in the country, holding naïve beliefs or hegemonic and patronizing attitudes about the peasantry and having little experience with real world politics. In fact, if their full life stories, especially the two decades before 1917, are taken into account, they and others of their generation were immersed in the activities of the zemstvo, local politics in general, and newspaper affairs. Their caution, moderate stances and gradualism were based not so much on inexperience as on long exposure to the peasantry and to the needs of the countryside as well as rather prescient awareness of the potential for catastrophe in the situation at that time.